History as art, art as history contemporary art and social studies education - Desai, Dipti; Hamlin, Jessica; Mattson, Rachel (New York, N.Y. Routledge, 2010)
This textbook pioneers methods for using contemporary works of art in the social studies and art classroom to enhance an understanding of visual culture and history. The interdisciplinary teaching tookit provides a pedagogical resource - complete with theoretical background and practical suggestions for teaching &.S. history topics through close readings of both primary sources and provocative works of contemporary art--Publisher.
Using Visual Historical Methods in the K-12 Classroom: Tactical Heuristics / by Rachel Mattson -- Curriculum as a Creative Process: An Interview with Artist-Educator Thi Bui / by Dipti Desai -- Artists in the Realm of Historical Methods: The Sound, Smell, and Taste of History / by Dipti Desai and Jessica Hamlin -- "Committing History in Public": Lessons from Artists Working in the Public Realm / by Jessica Hamlin and Dipti Desai -- Introduction to the Teaching Toolkits: Visual Approaches to Teaching about History -- Foundations of Citizenship -- Constructing Race -- The United States and the World.
Includes bibliographical references (pages [243]-245) and index.
Keywords: Art -- History -- Study and teaching; Art, Modern -- 21st century -- Study and teaching